2020
DOI: 10.3390/nu12113294
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Population-Level Consumption of Taxed and Non-Taxed Sugar-Sweetened Beverages (SSB) after Implementation of SSB Excise Tax in Thailand: A Prospective Cohort Study

Abstract: Background: Thailand has implemented a sugar-sweetened beverage (SSB) excise tax since September 2017, but questions remain about changes in individual-level SSB consumption after tax implementation. This study aimed to analyze the change in taxed and non-taxed SSB consumption in the Thai population. Method: This cohort study was carried out in 2018 and 2019. A total of 5594 persons who participated in both years were included in the analysis. Descriptive and t-test analyses were carried out in order to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 14 publications
3
20
0
Order By: Relevance
“…Higher tariffs on SSB lead children and adolescents to consume more fruit, vegetables and coffee as alternatives to SSB compared with their adult counterparts. Our results overlap with those of previous studies that reported an association between SSB taxes and increased consumption of fruits and vegetables (16) and coffee (46) . However, we found no evidence of the substitution of tea drinks for SSB by children and adolescents.…”
Section: Discussionsupporting
confidence: 62%
“…Higher tariffs on SSB lead children and adolescents to consume more fruit, vegetables and coffee as alternatives to SSB compared with their adult counterparts. Our results overlap with those of previous studies that reported an association between SSB taxes and increased consumption of fruits and vegetables (16) and coffee (46) . However, we found no evidence of the substitution of tea drinks for SSB by children and adolescents.…”
Section: Discussionsupporting
confidence: 62%
“…Finally, this research focused only on BMI and obesity prevalence. Recently, many studies have assessed the impact of SSB tax on consumption [ 51 ] and dental health [ 52 ]. However, it would be more beneficial if the analysis could cover other health indicators related to sugar consumption, such as obesity, type-2 diabetes, and cardiovascular disease (CVD) [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Thailand, beverages with a sugar content of 6 g or more per 100 ml are subject to varying tax rates (dependent on sugar content). Evaluation of this tax has revealed a 2.5% reduction in average purchases of sugar‐sweetened beverages, with greater reductions seen among children aged 6–14 years 108 . China has implemented fruit and vegetable production subsidies, paid to farmers and agricultural producers.…”
Section: Resultsmentioning
confidence: 99%
“…Evaluation of this tax has revealed a 2.5% reduction in average purchases of sugar-sweetened beverages, with greater reductions seen among children aged 6-14 years. 108 China has implemented fruit and vegetable production subsidies, paid to farmers and agricultural producers. While there are likely to be nutritional benefits to such a policy, it was implemented as a competitive measure and no evaluation of the nutrition flow-on effects have been conducted.…”
Section: Semi-structured Policy Auditmentioning
confidence: 99%